(untitled) (Journal of Brain and Spine Foundation Nepal, 2020)
Introduction: Incidence of stroke patients is increasing in low income countries like Nepal where management of these patients is challenging due to poor healthcare resources. Ischemic stroke is related to risk factors like age, male population, hypertension, diabetes mellitus, smoking and alcohol. Identification of these risk factors in the vulnerable population is important for prevention of ischemic stroke. The purpose of this study is to find out the social and demographic characteristics of patients with acute ischemic stroke treated at Upendra Devkota Memorial National Institute of Neurological and Allied Sciences, a tertiary care hospital of Nepal. Methods: Data was collected from all acute ischemic stroke patients presenting to the hospital over a period of one year. The age, sex, medical history of hypertension and diabetes and history of smoking and alcohol consumption were recorded. Statistical analysis of data was performed using Microsoft EXCEL 2019. Result: Total 310 patients were studied, out of which two-thirds were male. The highest number of patients were within the age group of 60-80 years with the mean age being 60 years. Hypertension and diabetes were present in 67.42% and 28.53% of patients respectively. 43.93% of the patients smoked while 33.87% of the patients consumed alcohol. Conclusion: Identification of association between risk factors like age, sex, hypertension, diabetes mellitus, smoking and alcohol consumption must be the emphasis for targeted preventive action to decrease the increasing burden of ischemic stroke among developing countries.